Penegakan Hukum terhadap Narapidana yang Melakukan Transaksi Narkotika di dalam Lembaga Pemasyarakatan - I Made Dwi Payana; Ida Ayu Putu Widiati; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2020)
Narcotics transaction or narcotics distribution, especially in correctional institutions has been very widespread; this is the impact of the loss of control of the existing system. This condition has an impact on the formation of a negative view of the community on the implementation of law enforcement, especially in the prison environment. So the problem under study is how to regulate sanctions related to narcotics transactions that occur within prison and how enforcement against inmates conducting drug transactions in prison law. By using the empirical normative legal research method (mix method) whit primary data sourced from Class II Penitentiary Kerobokan. The results of the study showed that the regulation of sanctions for prisoners who carry out narcotics transactions in prisons, namely the threat of capital punishment, life imprisonment, maximum imprisonment of 20 years and a minimum of 5 years. Whereas law enforcement in correctional institutions, namely severe disciplinary penalties, entered into a register, handed down register F, all prisoners’ rights will be lost, and passed on to the competent authority. The government in this case is the Ministry of Law and Human Rights should always collaborate with the National Narcotics Agency by visiting prisons regularly or allegedly as a place for narcotics transactions or distribution. Then with regard to legislation products that are already in force it should be noted again.